2009
DOI: 10.1111/j.1476-5381.2008.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction and functional selectivity of F15599, a preferential post‐synaptic 5‐HT1A receptor agonist

Abstract: Background and purpose: Activation of post-synaptic 5-HT1A receptors may provide enhanced therapy against depression. We describe the signal transduction profile of F15599, a novel 5-HT1A receptor agonist. ]-GTPgS binding more potently in frontal cortex than raphe. F15599, unlike 5-HT, more potently and efficaciously stimulated Gai than Gao activation. In rat prefrontal cortex (a region expressing post-synaptic 5-HT1A receptors), F15599 potently activated ERK1/2 phosphorylation and strongly induced c-fos mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
157
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(165 citation statements)
references
References 71 publications
(77 reference statements)
6
157
0
Order By: Relevance
“…In contrast, a recently reported and efficacious 5-HT 1A receptor agonist, 3-chloro-4-fluorophenyl-[4-fluoro-4-[[(5-methylpyrimidin-2-ylmethyl)amino]methyl]piperidin-1-yl]methanone (F15599), exhibits more than 1000-fold selectivity for 5-HT1 A receptors versus all other sites examined (Newman-Tancredi et al, 2009) and displays a distinctive preferential agonist activity at cortical 5-HT 1A sites. Indeed, F15599 preferentially activates immediate early gene (c-fos) expression in rat frontal cortex, while eliciting little or no activation in hippocampus or medial or dorsal raphe (Newman-Tancredi et al, 2009). In addition, F15599 stimulated the electrical activity of pyramidal neurons in frontal cortex at low doses (0.2 g/kg i.v.…”
Section: Anatomically Selective Targeting Of 5-ht 1a and 5-ht 2a Tranmentioning
confidence: 86%
“…In contrast, a recently reported and efficacious 5-HT 1A receptor agonist, 3-chloro-4-fluorophenyl-[4-fluoro-4-[[(5-methylpyrimidin-2-ylmethyl)amino]methyl]piperidin-1-yl]methanone (F15599), exhibits more than 1000-fold selectivity for 5-HT1 A receptors versus all other sites examined (Newman-Tancredi et al, 2009) and displays a distinctive preferential agonist activity at cortical 5-HT 1A sites. Indeed, F15599 preferentially activates immediate early gene (c-fos) expression in rat frontal cortex, while eliciting little or no activation in hippocampus or medial or dorsal raphe (Newman-Tancredi et al, 2009). In addition, F15599 stimulated the electrical activity of pyramidal neurons in frontal cortex at low doses (0.2 g/kg i.v.…”
Section: Anatomically Selective Targeting Of 5-ht 1a and 5-ht 2a Tranmentioning
confidence: 86%
“…Indeed, coimmunoprecipitation studies have indicated that 5-HT 1A receptors preferentially couple to distinct G-protein subtypes in different brain regions: G i in the dorsal raphe and other G-protein subtypes in other brain regions (38). Correspondingly, it has previously been shown that F13714 exhibited a distinctive signal transduction signature in vitro (39), leading to a preferential activation of presynaptic versus postsynaptic 5-HT 1A receptors. Thus, it is hypothesized that the capacity of agonist radiotracers to label 5-HT 1A receptors in different brain regions is associated with preferential interactions at receptors that couple to different Gprotein subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the differences observed here in the labeling patterns of comparison of 18 F-F13714 and 18 F-F15599 provide further evidence that these agonists distinguish 5-HT 1A receptor subpopulations in different brain areas. We are confident that the radiopharmacologic profile of 18 F-F13714 will be appropriate for clinical studies, taking into account its wellcharacterized pharmacology (27,30,39). A quantitative approach using kinetic models is now needed to complete this work.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the 5-choice serial reaction time task (5-CSRTT), Carli and Samanin (2000) combined a systemic dose of 8-OH-DPAT and dorsal raphe injection of the 5-HT 1A antagonist WAY 100635 to show that some of the effects of 8-OH-DPAT (slowing of responding and increased errors of omission) depend on the stimulation of postsynaptic 5-HT 1A receptors. Assié and colleagues compared the effects of the highly selective postsynaptic 5-HT 1A receptor agonist F15599 and the nonselective agonist F13714 and showed different relative effects on antidepressant-like activity (immobility in the forced swimming test) and 5-HT syndrome (forepaw treading and flat body posture) (Newman-Tancredi et al, 2009;Assié et al, 2010). These results suggest that the local application of 5-HT 1A receptor agonist is desirable to activate presynaptic 5-HT 1A receptors without affecting postsynaptic 5-HT 1A receptors.…”
Section: Discussionmentioning
confidence: 99%